ModGraph - Generating Executable EMF Models - Winetzhammer, Sabine (Electronic Communications of the EASST, 2012)
Model driven software engineering aims at creating high level executable models which may be interpreted or compiled. For efficient execution of operations on model instances code generators play an important role. A wellestablished tool for structural modeling and code generation is the Eclipse Modeling Framework (EMF). We extended EMF by behavior modeling within ModGraph, a tool to model behavior by graph transformation rules. Each rule corresponds to an operation modeled in the Ecore class diagram. This paper focuses on ModGraph’s code generator. Therefore I describe the matching of graph transformation rules as well as the exact translation of a rule and its seamless injection into the existing EMF Java code. A running example of a simple calendar application complements the explanation.